Structure and Evolution of Acinetobacter baumannii Plasmids - Salgado-Camargo, Abraham D.; Castro-Jaimes, Semiramis; Gutierrez-Rios, Rosa-Maria; Lozano, Luis F.; Altamirano-Pacheco, Luis; Silva-Sanchez, Jesús; Pérez-Oseguera, Ángeles; Volkow, Patricia; Castillo-Ramírez, Santiago; Cevallos, Miguel A. (Frontiers in Microbiology, 2020)
Acinetobacter baumannii is an emergent bacterial pathogen that provokes many types of infections in hospitals around the world. The genome of this organism consists of a chromosome and plasmids. These plasmids vary over a wide size range and many of them have been linked to the acquisition of antibiotic-resistance genes. Our bioinformatic analyses indicate that A. baumannii plasmids belong to a small number of plasmid lineages. The general structure of these lineages seems to be very stable and consists not only of genes involved in plasmid maintenance functions but of gene sets encoding poorly characterized proteins, not obviously linked to survival in the hospital setting, and opening the possibility that they improve the parasitic properties of plasmids. An analysis of genes involved in replication, suggests that each plasmid lineage represent a plasmid incompatibility group. The same analysis showed the necessity of classifying the Rep proteins in ten new groups, under the scheme proposed by Bertini and co-workers (2010). Also, we show that some plasmid lineages have the potential capacity to replicate in many bacterial genera including those embracing human pathogen species, while others seem to replicate only within the limits of the Acinetobacter genus. Moreover, some plasmid lineages are widely distributed along the A. baumannii phylogenetic tree. Despite this, a number of them lack genes involved in conjugation or mobilization functions. Interestingly, only 34.6% of the plasmids analyzed here possess antibiotic resistance genes and most of them belong to thirteen plasmid lineages of the twenty-three described here. Gene flux between plasmid lineages appears primarily limited to transposable elements, which sometimes carry antibiotic resistance genes. A. baumannii plasmids belong to a limited number of plasmid lineages and their structure seems to be very stable. Core genomes of plasmid lineages contain more genes that those required for plasmid maintenance functions. Our bioinformatic analyses suggest that each plasmid lineage represents a plasmid incompatibility group. In most plasmid lineages transposable elements and antibiotic resistance genes are secondary acquisitions. Finally, broad host-range plasmids appear to have played a crucial role.